Design of expert system for optimized protection studies against atmospheric discharges in distribution systems - Da Silva, I. N.; Flauzino, R. A.; C. Ulson, J. A. (Institute of Electrical and Electronics Engineers (IEEE), 2006)
The objective of this paper consists of presenting a design of expert system that assists the procedures involved with the protection specification of transformers and equipments against atmospheric discharges, allowing also analyze in a detailed and systematic way the behavior of the respective voltage transients that are generated at the supplying area which belongs to Bandeirante Energy. For such purpose, the expert system developed in this research makes the efficient integration of approaches and techniques that take into account the characteristic aspects of the atmospheric discharges, the experimental analyses that represent the phenomenon and the mathematical models that allow to map the process involved with the formation of the lightning. © 2006 IEEE.
Keywords: Distribution lines; expert systems; lightning; system protection; transformer